The Use of the String of Pearls Locking Plate System in the Stabilisation of a Comminuted Calcaneal Fracture in a Giant Breed Dog - A. B. Scrimgeour; A. J. Worth (Case Reports in Veterinary Medicine)
An eight-year-old male Pyrenean mountain dog was presented with a comminuted fracture of the right calcaneus following motor vehicle trauma. The fracture was stabilised with a plate-rod construct, using the String of Pearls locking plate system and an intramedullary pin. Healing was uncomplicated.